2005
DOI: 10.1007/s10694-005-4050-y
|View full text |Cite
|
Sign up to set email alerts
|

Fire Spread Between Vehicles in Tunnels: Effects of Tunnel Size, Longitudinal Ventilation and Vehicle Spacing

Abstract: In a number of catastrophic tunnel fire incidents, the fire has often spread from vehicle to vehicle over large distances, occasionally hundreds of metres. Five possible means of fire spread are briefly discussed. The paper focuses on fire spread by flame impingement and investigates the conditions under which flame impingement will occur on a 4 m high HGV downstream of the initial fire. The study uses Bayesian methods to predict the probability of impingement at distances from 0 to 20 m downstream, based on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…24 For example, in the St. Gotthard fire accident in Switzerland, it involved two crashed vehicles and the nearest heavy goods vehicle (HGV) quickly caught on fire even though it was 30 m away from the initial fire source. 25 Under such conditions, the fire behaviors can be very different from those with single fire source, 26,27 while the critical ventilation velocity changes accordingly. This could be much dependent on the distance of these two fire sources, as the two fire plumes can interact with each other, resulting in different HRR s, temperature distribution, and smoke back-layering.…”
Section: Introductionmentioning
confidence: 99%
“…24 For example, in the St. Gotthard fire accident in Switzerland, it involved two crashed vehicles and the nearest heavy goods vehicle (HGV) quickly caught on fire even though it was 30 m away from the initial fire source. 25 Under such conditions, the fire behaviors can be very different from those with single fire source, 26,27 while the critical ventilation velocity changes accordingly. This could be much dependent on the distance of these two fire sources, as the two fire plumes can interact with each other, resulting in different HRR s, temperature distribution, and smoke back-layering.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the critical HRR (Q fc ) for spread in a tunnel similar in size to the Channel Tunnel increases with increasing ventilation velocity, but Q fc is considerably less when assuming flame impingement. However, it has also been found from a study that increasing velocity increases the probability of flame impingement (Carvel et al, 2005).…”
Section: The Influence Of Ventilation On Fire Spreadmentioning
confidence: 93%
“…Due to the lack of systematic experimental data, the authors declared early that when new data becomes available the results will be refined. This has also been done in publications such as references [42,43].…”
Section: Influence Of Ventilation On Maximum Heat Release and Fire Grmentioning
confidence: 99%